Fine scale variations of surface water chemistry in an ephemeral to perennial drainage network. Issue 24 (12th July 2012) - Zimmer, Margaret A.; Bailey, Scott W.; McGuire, Kevin J.; Bullen, Thomas D.
Abstract: Although temporal variation in headwater stream chemistry has long been used to document baseline conditions and response to environmental drivers, less attention is paid to fine scale spatial variations that could yield clues to processes controlling stream water sources. We documented spatial and temporal variation in water composition in a headwater catchment (41 ha) at the Hubbard Brook Experimental Forest, NH, USA. We sampled every 50 m along an ephemeral to perennial stream network as well as groundwater from seeps and 35 shallow wells across varying flow conditions. Groundwater influences on surface water in this region have not been considered to be important in past studies as relatively coarse soils were assumed to be well drained in steep catchments with flashy runoff response. However, seeps displayed perennial discharge, upslope accumulated areas (UAA) smaller than those for channel initiation sites and higher pH, Ca and Si concentrations than streams, suggesting relatively long groundwater residence time or long subsurface flow paths not bound by topographic divides. Coupled with a large range in groundwater chemistry seen in wells, these results suggest stream chemistry variation reflects the range of connectivity with, and quality of, groundwater controlled by hillslope hydropedological processes. The magnitude of variations of solute concentrations seen in the first order catchment was as broad as that seen at the fifth order Hubbard Brook Valley (3519 ha). Reduction in variation in solute concentrations with increasing UAA suggested a representative elementary area (REA) value of less than 3 ha in the first order catchment, compared with 100 ha for the fifth order basin. Thus, the REA is not necessarily an elementary catchment property. Rather, the partitioning of variation between highly variable upstream sources and relatively homogenous downstream characteristics may have different physical significance depending on the scale and complexity of the catchment under examination. Copyright © 2012 John Wiley & Sons, Ltd.